2001
DOI: 10.1385/abab:90:3:199
|View full text |Cite
|
Sign up to set email alerts
|

Lichenysin: A More Efficient Cation Chelator Than Surfactin

Abstract: The lipopeptide lichenysin (cyclo-[L-Gln1-->D-Leu2-->L-Leu3-->L-Val4--> L-Asp5-->D-Leu6-->L-Ile7-beta-OH fatty acid]) produced by Bacillus licheniformis structurally resembles surfactin from Bacillus subtilis. The main difference is the presence of a glutaminyl residue in position 1 of the peptide sequence in place of glutamic acid in surfactin. This local variation causes significant changes in the properties of the molecule compared to surfactin. Lichenysin has a higher surfactant power, the critical micella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 18 publications
0
88
0
Order By: Relevance
“…Huang et al, (2007) reported that a lipopeptide antimicrobial substance produced by B. subtilis fmbj strain, which is mainly composed of surfactin and fengycin, was able to inactivate endospores of B. cereus through damaging the surface structure of the spores as seen by Transmission Electron Microscopy. Lichenysin, pumilacidin and polymyxin B (Grangemard et al, 2001;Landman et al, 2008;Naruse et al, 1990;Yakimov et al, 1995) are other antimicrobial lipopeptides produced by Bacillus licheniformis, Bacillus pumilus and Bacillus polymyxa, respectively. Polymyxin B, in particular, due to its high affinity for the lipid moieties of lipopolysaccharide, has shown antibacterial activities against a wide variety of Gram-negative pathogens.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Huang et al, (2007) reported that a lipopeptide antimicrobial substance produced by B. subtilis fmbj strain, which is mainly composed of surfactin and fengycin, was able to inactivate endospores of B. cereus through damaging the surface structure of the spores as seen by Transmission Electron Microscopy. Lichenysin, pumilacidin and polymyxin B (Grangemard et al, 2001;Landman et al, 2008;Naruse et al, 1990;Yakimov et al, 1995) are other antimicrobial lipopeptides produced by Bacillus licheniformis, Bacillus pumilus and Bacillus polymyxa, respectively. Polymyxin B, in particular, due to its high affinity for the lipid moieties of lipopolysaccharide, has shown antibacterial activities against a wide variety of Gram-negative pathogens.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Putisolvins I and II were shown (i) to reduce the surface tension of the medium, (ii) to increase the formation of an emulsion with toluene, (iii) to stimulate were reported to permeabilize membranes, resulting in pore formation and haemolysis (Grangemard et al, 2001) and to play a role in bacterial attachment to surfaces (Neu, 1996). Lipopeptides produced by Serratia (Lindum et al, 1998) and Burkholderia (Huber et al, 2002) were shown to be essential for the stimulation of swarming motility and thus could contribute to the regulation of biofilm formation (Huber et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…22;23 Surfactin is also an effective antimicrobial and antiviral agent, able to induce formation of ionic pores in phospholipid bilayers, 24 and transport cations across membranes. 25 Its cation-complexing property, due to two negative charges on the aspartyl and glutamyl residues, is probably fully utilized in systems containing ubiquitous amounts of Ca ++ and Na + ions.…”
Section: Screening and Characterization Of Biological Surfactantsmentioning
confidence: 99%
“…Figure 11 shows porosity and permeability values for all the cores characterized to date, overlaid on similar data from Watney (1994). 25 Watney characterized Bethany Falls and Mound Valley oolites and found a wide range of porosity and permeability. Dubois et al 24 noted that the LKC was very similar to modern Caribbean oolites and our experimental data for moldic LKC outcrop and reservoir cores, as well as Miami and Joulters Cay oolite agree well with the published values for similar material.…”
Section: Characterization Of Core Materialsmentioning
confidence: 99%